Creating value-added solutions to highlands produce - de Gula, Cerwin Andrada (Animo Repository, 2021)
In the Philippines, substantial farm losses and food wastages have been reported due to oversupply and quality rejections. This insider action research has aimed at the reduction of farm harvest losses and wastages by giving the farmers a solution to add value to their wastes. In the completed cycles, One Concord Food Solutions Inc. and Session Groceries created training programs that provided lessons on food processing. The team used the ADDIE Model of Instructional Design (Analysis, Design, Development, Implementation, Evaluation) as a guide for effective training. The first cycle was a mix of online and face-to-face learning sessions. During this cycle, the objective was to reduce farm harvest wastage and losses. The instructors are different subject matter experts on various topics on food processing. The 7-module program consisted of courses like food safety, food microbiology, food packaging, processing mathematics, marketing, and regulatory compliance. The team did not achieve the goal in this cycle and decided to proceed with Cycle 2. The second Cycle had the same objective as cycle 1. With the same goal, the team prepared a new training program as a supplement to the first. Hands-on activities and the development of products from available farm produce are the spotlights of cycle 2. Through collaborative efforts, products such as Fresh Basil Pesto, Ready-to-drink Celery Juice, and Real Mayonnaise were produced. Product labels were also designed and developed following standard pre-packaged food labeling requirements. The objective was achieved; farmers who attended the cycle two training were able to utilize excess farm harvest and rejected produce and convert them into processed food products. In the broader context, the researcher explored the possibility of adding some elements to the existing ADDIE Model to make the training program more a constructivist approach. Through reflections, the researchers understood that the key to a successful training program is a collaboration between the instructors and the learners.